Implementation of Urban Open Space as an Active Recreational Area on West Java Art and Cultural Center - Faizah Rasya Zita (Universitas Trisakti, 2019)
Among the physical that facilitace urban development, public open space is singularly responsible for improving urban quality. Open Space is an elongated area / lane and / or group, which used by the community. Open Space can create a character of urban society for social interaction that can united all members of the community without distinguishing social, economic and cultural backgrounds. The observation proves that area surrounding west java art and cultural center does not have an open space area that can facilitate social interaction between community members. This causes a slums around the site area which can’t be used by the comunnity to enjoyed. Therefore, it is necessary to design an open space in the outside of west java art and cultural center building, that can be used as an active recreational area to accommodate public activities as much as possible.